Forced draught supercritical carbon dioxide cooling system performance - Boshoff, Francois Daneel (Stellenbosch : Stellenbosch University, 2025)
Boshoff, F. D. 2025. Forced draught supercritical carbon dioxide cooling system performance. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/4368ce76-3ec7-455e-97c5-c717e04f7215